O comércio eletrônico no negócio de turismo - Reis, Marcos Antonio dos (2011)
Modern organized society lives in a crescently globalized and informatized world, where competitiveness among companies grows stronger every day. At the same time, potential and effective clients are more demanding and more informed about the products and the corporations. Internet has showed itself as a very important strategic tool in the transformation of the markets and the consumption chain, causing changes and forcing companies to rethink its business models. Electronic commerce is an emerging giant, having moved, throughout the world, US$ 502,1 billion in 2009, with an estimate projection of US$ 963 billion in 2013 - an annual growth rate around 19,5% (source: www.ecommercenew.com.br). Tourism, in the view of the client, is formed by information that is largely available in the internet. Everyday new companies are formed using the internet as a business marketplace in the tourism sector. Some companies offer its products exclusively on the internet, while others still use the traditional means. This research studies some practices of the tourism sector in Brazil, aiming to obtain a more clear perception on the impact and influence of the internet over it. Evidences possible causes and effects of internet's utilization and its non utilization as a marketplace, an important mean of communication and the business models derived from it. Finally, it tries to offer a clear sight of its role together with the e-commerce in the consolidation of the tourism business in Brazil